2020
DOI: 10.3390/ijerph17041180
|View full text |Cite
|
Sign up to set email alerts
|

Particle and Carbon Dioxide Concentration Levels in a Surgical Room Conditioned with a Window/Wall Air-Conditioning System

Abstract: One of the most important functions of air conditioning systems in operating rooms is to protect occupants against pathogenic agents transported by air. This protection is done by simultaneously controlling the air distribution, temperature, humidity, filtration and infiltration from other areas etc. Due to their low price, simple installation, operation and maintenance, window/wall air conditioning system have largely been used in operating rooms in Brazil, even if these types of equipment only recirculate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Our findings show that indoor air CO 2 concentrations in our hospital commonly peaked above recommended levels, providing a rationale for widespread use of CO 2 monitors in patient rooms and clinical areas. These results are in line with previous reports in the literature (Baures et al, 2018;Chang et al, 2013;Jung et al, 2015;Pereira et al, 2020;Tang et al, 2009;Zhou et al, 2015) and are thus likely widely generalizable to many acute hospital wards worldwide. Of course, there are also many modern hospital wards with superior HVAC systems and excellent overall ventilation (as seen in intensive care units for example) (Kenarkoohi et al, 2020;Vosoughi et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings show that indoor air CO 2 concentrations in our hospital commonly peaked above recommended levels, providing a rationale for widespread use of CO 2 monitors in patient rooms and clinical areas. These results are in line with previous reports in the literature (Baures et al, 2018;Chang et al, 2013;Jung et al, 2015;Pereira et al, 2020;Tang et al, 2009;Zhou et al, 2015) and are thus likely widely generalizable to many acute hospital wards worldwide. Of course, there are also many modern hospital wards with superior HVAC systems and excellent overall ventilation (as seen in intensive care units for example) (Kenarkoohi et al, 2020;Vosoughi et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Few studies have reported indoor CO 2 concentrations in hospitals (Shajahan et al, 2019). Inappropriately high CO 2 concentrations were measured in hospitals without modern HVAC systems (Hwang and Park, 2020;Lee et al, 2020;Pereira et al, 2020;Zaman et al, 2021;Zhou et al, 2015). In contrast, excellent CO 2 values have been reported in COVID-19 wards without detectable airborne viral genomes (Vosoughi et al, 2021) and an Iranian intensive care unit (where viral genomes were still detected in N = 2/14 air samples) (Kenarkoohi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In-door air quality is affected by a variety of factors including human occupation [1][2][3]. Developing and applying effective and non-invasive methods that monitor the amount of people in a room is particularly important in clinical settings where air quality is a major factor that can contribute to nosocomial infection including surgical site infections [4][5]. It has been reported that 2.0-2.4% of all total joint arthroplasties in the U.S. result in periprosthetic infection, [6] which imposes signi cant morbidity on patients and large nancial burdens on the healthcare system, [7] making the pursuit of improved air quality in operating rooms of high importance.…”
Section: Introductionmentioning
confidence: 99%
“…Besides being a greenhouse gas in the atmosphere, carbon dioxide (CO 2 ) also plays an important role in indoor environments [1][2][3][4][5][6][7]. CO 2 is an indoor air quality indicator [8][9][10][11][12][13][14][15][16][17][18]. CO 2 is the principal product of the combustion of fossil fuels and biomass.…”
Section: Introductionmentioning
confidence: 99%